Conflict between Liberal Economic Ideology and Citizenship at Work - Murray, Georgina (Relations industrielles / Industrial Relations, 2005)
Citizenship in work is a continuous process of sustaining and fighting for just social rights. The argument here is that currently a major impediment to this democratic process at work is the practical and ideological imposition of economic liberal policy, conceived for and by dominant class interests. This article discusses the idea of citizenship, its antithesis economic liberalism and its synthesis Keynesianism and the welfare state. Then it asks what these and other ideas bring to the debate about citizenship and work in a global society?